High nitrous oxide (N2O) greenhouse gas reduction potential of Pseudomonas sp. YR02 under aerobic condition. (June 2023) - Wang, Yuren; Deng, Min; Li, Biqing; Li, Lu; Oon, Yoong-Sin; Zhao, Xiaoli; Song, Kang
Graphical abstract: Highlights: Strain YR02 bioaugmentation mitigated 98.7% of N2 O emission in a WWTP. V max, N 2 O of strain YR02 is 3.6–128.4 times higher than other N2 O reducers. The optimal C/N ratio for N2 O reduction (C/N = 5) is 1/3 of that for IN removal. The modified Gompertz model indicated IN utilization priority was TAN > NO3 –  > NO2 – . The optimal conditions for inorganic nitrogen and N2 O removal were obtained. Abstract: Aerobic environments exist widely in wastewater treatment plants (WWTP) and are unfavorable for greenhouse gas nitrous oxide (N2 O) reduction. Here, a novel strain Pseudomonas sp. YR02, which can perform N2 O reduction under aerobic conditions, was isolated. The successful amplification of four denitrifying genes proved its complete denitrifying ability. The inorganic nitrogen (IN) removal efficiencies (NRE) were >98.0% and intracellular nitrogen and gaseous nitrogen account for 52.6–58.4% and 41.6–47.4% of input nitrogen, respectively. The priority of IN utilization was TAN > NO3 – -N > NO2 – -N. The optimal conditions for IN and N2 O removal were consistent, except for the C/N ratio, which is 15 and 5 for IN and N2 O removal, respectively. The biokinetic constants analysis indicated strain YR02 had high potential to treat high ammonia and dissolved N2 O wastewater. Strain YR02 bioaugmentation mitigated 98.7% of N2 O emission and improved 32% NRE in WWTP, proving its application potential for N2 O mitigation.